2008
DOI: 10.1111/j.1553-2712.2008.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Retention Rates after Training in Posterior Epistaxis Management

Abstract: Objectives: The objective of the study was to compare the learning and retention rates of resident physicians trained in posterior epistaxis management with nasal gauze packing on a simulation model following two training methods.Methods: This was a prospective, repeated-measures study. An objective, criterion-referenced performance standard, consisting of the number of major steps completed in the proper sequence, and the number of minor steps completed within a specified time, was used by an evaluator to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 26 publications
0
39
0
3
Order By: Relevance
“…23 This study found that those trained using the mastery model completed the test task faster (effect size = 0.59, p = 0.003) and with better technique (effect size = 0.40, p < 0.001) compared with the nonmastery group. As above, these positive effects were not seen when subjects were tested 3 months later.…”
Section: Comparison Between Alternate Types Of Technologyenhanced Simmentioning
confidence: 83%
See 2 more Smart Citations
“…23 This study found that those trained using the mastery model completed the test task faster (effect size = 0.59, p = 0.003) and with better technique (effect size = 0.40, p < 0.001) compared with the nonmastery group. As above, these positive effects were not seen when subjects were tested 3 months later.…”
Section: Comparison Between Alternate Types Of Technologyenhanced Simmentioning
confidence: 83%
“…23,24 Lammers 23 used a "pause and perfect" model for teaching posterior epistaxis management, with faculty supervising participants during each step of a procedure, and pausing to correct mistakes when they were evident. When compared with trainees who received traditional observation, intervention subjects were more efficient and had better technique; this effect, however, was not sustained when subjects were retested at 3 months.…”
Section: Comparison Between Alternate Types Of Technologyenhanced Simmentioning
confidence: 99%
See 1 more Smart Citation
“…9,22 However, other studies of simulator-based training interventions have demonstrated significant skill decay over time. 23,24 Our intervention includes a standardized curriculum with intense deliberate practice, which we believe is responsible for the substantial skill retention as seen in other similarly successful interventions. 25 Our finding is made more evident by comparing results for the 2008 cohorts with those for similarly studied resident cohorts in 2004, where simulator-trained PGY-2 residents performed significantly better than traditionally trained (non-SBME trained) PGY-3 residents.…”
Section: Discussionmentioning
confidence: 99%
“…60 More recently, educators are using HF more overtly in addressing procedures 61 and also indirectly through the measurement of learner cognitive load during the training process. 29,30 Investigators have utilized HFA to approach simulation-based training and assessment of procedures, including intraosseous line insertion, 62 epistaxis management, 63 bag-valve-mask ventilation, 64 intravenous catheter insertion, 65 emergency ultrasound technique, 66 and central venous catheter placement.…”
Section: Hf In Emmentioning
confidence: 99%